Effect of Parkinson's disease on primary total joint arthroplasty outcomes: A meta-analysis of matched control studies. (November 2019) - Min, Huan; Lin, Hui; Chen, Gang
Abstract: Background: Currently, no meta-analysis exists elucidate the outcomes of total joint arthroplasty (TJA) in patients with Parkinson's disease (PD). The aim of this study was to investigate the outcomes of TJA in patients with PD with respect to complication and revision in comparison to a TJA cohort without PD. Methods: MEDLINE, Scopus, EMBASE, and Cochrane Library databases were searched with English language restrictions. The primary outcome measures were complications and revision, whereas the secondary outcomes included length of stay (LOS) and total charge. Results: Seven studies with a total of 124163 patients were included. The most important finding from our study was that PD patients had a 42% higher risk for any medical complication ( P = 0.004) and a 65% higher risk for any surgical complication ( P = 0.01) compared to the matched cohort. Specifically, PD was associated with increased superficial wound infection ( P = 0.006), dislocation ( P = 0.01), deep vein thrombosis (DVT) ( P = 0.02), LOS ( P = 0.0005), and total hospital charges ( P < 0.00001). However, PD did not increase the risks for periprosthetic infection ( P = 0.32) and revision ( P = 0.17). Conclusions: Patients with PD are at increased risk for medical complication and surgery complications, particularly superficial wound infection, dislocation, and DVT as compared to patients without PD. PD patients also exhibit increased LOS and total hospital charges. However, PD did not increase the risks for periprosthetic infection and revision. Highlights: Patients with PD are at increased risks compared to patients without PD. PD patients also exhibit increased length of stay and total hospital charges. PD did not increase the risks for periprosthetic infection and revision.